'Berlusconi's Italy': the media between structure and agency. Issue 1 (February 2015) - Padovani, Cinzia
Abstract : In this article, I explore the conditions of the media in Italy by taking into consideration a variety of elements: the context of media legislation and media concentration that have favoured the interests of Silvio Berlusconi, and the role of progressive agency (media professionals, citizens' groups) as they worked within those constraints to keep alive the flames of democracy during the 'Berlusconi era'. This perspective is intended to provide an alternative interpretation to what has become the prevailing view of contemporary Italy: an 'abnormal' country; the 'Sick Man of Europe'; worse yet: a country of 'servants'. The framework of analysis includes the influence of the media-magnate-turned-politician on media legislation and the television sector, but also evaluates the important roles that media professionals and citizens have played to improve pluralism. The article argues that despite extreme levels of media concentration and an unprecedented conflict of interests, a commitment to engage in political discourse has continued to characterise Italy's political culture. This commitment has been expressed by a multiplicity of actors, from journalists and media professionals to citizens' organisations and media activists.